2015
DOI: 10.1111/ajad.12245
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine enhances and accelerates the expression of sensitization induced by coca paste indicating its relevance as a main adulterant

Abstract: Results may shed light on the fast and high dependence observed in CP users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Exposure to caffeine increases the psychomotor stimulant effects of amphetamine (Cauli et al 2003;Palmatier et al 2003;Simola et al 2006), nicotine (Celik et al 2006;Gasior et al 2000), and cocaine (López-Hill et al 2011;Misra et al 1986;Prieto et al 2015). However, this effect does not explain our results since the increase in responding of the coc + caff group was restricted to the active nosepoke, whereas inactive nosepoke responding remained low at all times.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Exposure to caffeine increases the psychomotor stimulant effects of amphetamine (Cauli et al 2003;Palmatier et al 2003;Simola et al 2006), nicotine (Celik et al 2006;Gasior et al 2000), and cocaine (López-Hill et al 2011;Misra et al 1986;Prieto et al 2015). However, this effect does not explain our results since the increase in responding of the coc + caff group was restricted to the active nosepoke, whereas inactive nosepoke responding remained low at all times.…”
Section: Discussionmentioning
confidence: 57%
“…Cocaine doses were chosen based on previous data (Valentini et al 2013). Caffeine doses were selected to mimic a dose ratio found in seized samples of cocapaste (López-Hill et al 2011;Prieto et al 2015) or in other street samples as reported in literature (see an overview at http://www.drugsandalcohol.ie/13119/).…”
Section: Drugs and Dosesmentioning
confidence: 99%
See 3 more Smart Citations